Successful Surgical Treatment of a Septuagenarian with Anomalous Right Coronary Artery from the Pulmonary Artery with an Eleven Year Follow-Up: Case report and review of literature - Kuba, Paresh Kumar (Sultan Qaboos University Medical Journal, College of Medicine & Health Sciences, 2013)
An anomalous origin of the right coronary artery from the pulmonary artery (ARCAPA) is a very rare coronary artery anomaly with only 98 cases reported in literature till date. We report the oldest surgically treated patient and the fourth ever septuagenarian with this anomaly diagnosed ante-mortem with an eleven year follow-up. The literature on this anomaly was reviewed and discussed to highlight the clinical implications.